2016
DOI: 10.1074/jbc.m115.711697
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Essential Modulator (NEMO) Is Critical for Thyroid Function

Abstract: The I-B kinase (IKK) subunit NEMO/IKK␥ (NEMO) is an adapter molecule that is critical for canonical activation of NF-B, a pleiotropic transcription factor controlling immunity, differentiation, cell growth, tumorigenesis, and apoptosis. To explore the functional role of canonical NF-B signaling in thyroid gland differentiation and function, we have generated a murine strain bearing a genetic deletion of the NEMO locus in thyroid. Here we show that thyrocyte-specific NEMO knock-out mice gradually develop hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…These characteristics match very well to those found in Xenopus laevis using MO antisense oligomers exhibiting a hypoplastic thyroid anlage ( Fig. 3) and to those found in NEMOTS-KO thyrocytes undergoing progressive apoptosis after birth [20]. Moreover, patients with hypohydrotic ectodermal dysplasia develop primary hypothyroidism in infancy [21][22][23].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These characteristics match very well to those found in Xenopus laevis using MO antisense oligomers exhibiting a hypoplastic thyroid anlage ( Fig. 3) and to those found in NEMOTS-KO thyrocytes undergoing progressive apoptosis after birth [20]. Moreover, patients with hypohydrotic ectodermal dysplasia develop primary hypothyroidism in infancy [21][22][23].…”
Section: Discussionsupporting
confidence: 86%
“…In fact, NF-kB controls the expression of thyroid proteins, including sodium iodide symporter, TTF 1/NKX2-1, PAX8, TPO, and TG. It was concluded that IKBKG-dependent signaling is essential for thyrocyte survival and maintenance of thyroid marker expression [20,28]. These findings may also reflect the potential role of the complex TRPC4AP/ IKBKG in the pathophysiology of congenital primary thyroid disease with deteriorating postnatal thyroid function.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Right kidney was embedded in paraffin and 4 μm sections were stained with hematoxylin and eosin (Sigma‐Aldrich, Milan, Italy) according to the manufacturer's instructions. The immunoperoxidase and immunofluorescence were performed as already described . For immunoperoxidase and immunofluorescence staining the following primary antibodies were used: rabbit anti‐Cyclin D1 H‐295 (sc 753, Santa Cruz) dilution 1:50; rabbit anti‐c‐Myc (ab 32072, Abcam) dilution 1:100; rabbit anti‐ERK1 (C‐16) (sc 93, Santa Cruz) dilution 1:50; rabbit anti‐phospho P44/42 (Thr202‐T204) (9101S, Cell Signaling) dilution 1:50.…”
Section: Methodsmentioning
confidence: 99%